Implementation of Group Picture Guessing Learning Method to Improve Children's Language Skills - Dewi Pusparini; Hotimatul Hosna; Mediyana (Public Service: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study aims to describe the implementation of the method of learning language skills in children in group guessing games through group guessing games in improving children's language skills at PAUD An-Nawawi, Larangan Slampar Village, Tlanakan District, Pamekasan Regency. The background of this study is the importance of developing language skills at an early age as a basis for the subsequent learning process in the development of their language skills. The method used in this study is a qualitative approach with a type that is implemented in two cycles. Each cycle consists of the planning, implementation, observation, and reflection stages. The subjects in this study were children in group A at PAUD An-Nawawi totaling 15 children. The results of the study showed that the application of the method of learning children's language skills in group guessing games can improve children's language skills, both in terms of the ability to name objects, or animals to compose simple sentences, and in children's courage to speak in front of peers. This increase is shown through the results of observations that show a significant increase in aspects of language development after the method was implemented. Thus, it can be concluded that group guessing games are an effective method for improving the language skills of early childhood.